Is fetal CTG a reliable indicator of fetal distress? A prospective study on relationship between CTG suspected fetal distress and immediate postpartum umbilical cord blood pH. - Kanika Gupta; Arpana Haritwal; Bela Makhija; Ruchi Bhandari (National Scientific Medical Center, 2022)
Introduction Perinatal asphyxia is one of the major causes of neonatal morbidity and mortality. Fetal Cardiotocography (CTG) has been used for long to predict fetal asphyxia. Despite its popularity, it has not been proved to be an ideal tool for monitoring as, although a normal trace is indicative of a normal acid-base status at birth, in about 98% of cases, an abnormal trace has a low positive predictive value in term of fetal acidosis (pH less than 7.25) .An undisputed evidence of perinatal asphyxia is metabolic acidosis on arterial cord blood or very early neonatal samples: pH< 7 and base deficit >12 mmol/L Aim To see the correlation between suspicious/pathological CTG and umbilical cord blood pH at birth in term pregnancies. Material and methods This was a hospital based prospective randomized observational study over a period of 1 year. It was conducted on 165 pregnant women with singleton term pregnancy admitted to labour ward for delivery and having suspicious / pathological CTG trace or meconium stained liquor with normal CTG trace. Immediately after the birth of the neonate, umbilical cord was clamped, cut and umbilical artery cord blood was collected in a pre - heparinized syringe and sent for pH analysis. Cord blood pH of less than 7.2 was interpreted as acidosis. Results The number of acidotic cases (as determined by cord blood pH less than 7.2) was 2(5.6%) in normal traces whereas 34 cases (94.4%) of normal traces were non acidotic. In the suspicious traces, 2 cases (3.2%) were acidotic and 59 cases (96.8%) were non acidotic. In the pathological category, 13 cases (19.1%) were acidotic and 55 cases (80.9%) were non acidotic. There was no significant association of CTG category with cord blood pH, acidosis, pO2 or pCo2 values but that with presence of MSL and grade of MSL was statistically significant. Conclusion Abnormal CTG while being a good predictor of the presence of MSL and also the grade of MSL, is a poor predictor of the presence of fetal acidosis and neonatal status after birth. Fetal monitoring using cardiotocography was associated with considerable false positive results. Thus, using fetal heart rate abnormalities alone as a measure of diagnosis of fetal distress during labour is a contributing factor of increasing rate of cesarean sections.